Chapter Nederlandse Southern Gothic - Andeweg, Agnes (Amsterdam University Press, 2023)
This article presents a close reading of gothic features in Simone Atangana Bekono's novella Zo hoog de zon stond ('As high as the sun stood', 2022). This analysis serves as a way to comment on recent academic debates about the end, or ends, of critical theory, more specifically about ways of reading: surface reading or symptomatic reading. Supporting Esther Peeren's recent plea for a return to symptomatic reading, I argue that a clearcut opposition between surface and depth is untenable.